Portal vein surgical treatment on non-tumoral portal vein thrombosis in liver transplantation: Systematic Review and Meta-Analysis (Clinics, 2021)
Non-tumoral portal vein thrombosis (PVT) is associated with higher morbidity and mortality in liver transplantation (LT). In this study, we aimed to evaluate the impact of PVT in LT outcomes and analyze the types of surgical techniques used for dealing with PVT during LT. A systematic review was conducted in Cochrane, MEDLINE, and EMBASE databases, selecting articles from January 1990 to December 2019. The MESH-terms used were (‘‘Portal Vein’’[Mesh] AND ‘‘Thrombosis’’[Mesh] NOT ‘‘Neoplasms’’[Mesh]) AND (‘‘Liver Transplantation’’[Mesh]). The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) recommendation was used, and meta-analysis was performed with Review Manager Version 5.3 software. A total of 1,638 articles were initially found: 488 in PubMed, 289 in Cochrane Library, and 861 in EMBASE, from which 27 were eventually selected for the meta-analysis. Surgery time of LT in patients with PVT was longer than in patients without LT (po0.0001). Intraoperative red blood cell (po0.00001), fresh frozen plasma (p=0.01), and platelets (p=0.03) transfusions during LT were higher in patients with PVT. One-year (odds ratio [OR] 1.17; p=0.002) and 5-year (OR 1.12; p=0.01) patient survival after LT was worse in the PVT group. Total occlusive PVT presented higher mortality (OR 3.70; p=0.00009) and rethrombosis rates (OR 3.47 [1.18–10.21]; p=0.02). PVT Yerdel III/IV classification exhibited worse 1-year [2.04 (1.21–3.42); p=0.007] and 5-year [0.98 (0.59–1.62); p=0.93] patient survival. Thrombectomy with primary anastomosis was associated with better outcomes. LT in patients with non-tumoral PVT demands more surgical time, needs more intraoperative transfusion, and presents worse 1- and 5-year patient survival. Total occlusive PVT and Yerdel III/IV PVT classification were associated with higher mortality. (PROSPERO, registration number: CRD42020132915).